2005
DOI: 10.1111/j.1365-2648.2005.03477.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and nurses’ perceptions of nursing problems in an acute care setting

Abstract: Nurses need to be more aware that patients and nurses often hold disparate views of the priorities in nursing care. To plan individualized nursing care effectively, nurses need to elicit and use individual patients' preferences more systematically in care planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
3
8

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 38 publications
(73 reference statements)
4
73
3
8
Order By: Relevance
“…Current studies in the literature related to decision making in discharge planning focus on the decision to refer a patient to post-hospital services (Bowles, Foust, & Naylor, 2003; Jette, Grover, & Keck, 2003) and perceptions and knowledge about the discharge planning process in general (Florin, Ehrenberg, & Ehnfors, 2005; Tilus, 2002). Recent systematic reviews of discharge planning activities and interventions concluded that insufficient evidence (beyond expert opinion-based standards of practice) currently exists to guide practice changes (Maramba, Richards, Myers, & Larrabee, 2004; Mistiaen, Francke, & Poot, 2007; Shepperd, Parkes, McClaran, & Phillips, 2004).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Current studies in the literature related to decision making in discharge planning focus on the decision to refer a patient to post-hospital services (Bowles, Foust, & Naylor, 2003; Jette, Grover, & Keck, 2003) and perceptions and knowledge about the discharge planning process in general (Florin, Ehrenberg, & Ehnfors, 2005; Tilus, 2002). Recent systematic reviews of discharge planning activities and interventions concluded that insufficient evidence (beyond expert opinion-based standards of practice) currently exists to guide practice changes (Maramba, Richards, Myers, & Larrabee, 2004; Mistiaen, Francke, & Poot, 2007; Shepperd, Parkes, McClaran, & Phillips, 2004).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…According to the code of ethics for nurses (2005), adopted by the International Council of Nurses, respect for the individuality and uniqueness of all persons receiving nursing care is a nursing obligation. Although being cared for as an individual is important for patients (Radwin, 2000;Suhonen et al, 2002), the provision of nursing care is not always so (Attree, 2001;Florin et al, 2005;Muntlin et al, 2006). At times, when practice is governed by clinical guidelines and standardized protocols (Jones and Kamath, 1998;Woolf et al, 1999), especially in surgical care (Sade et al, 2000), questions related to individuality in care are of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of emphasis on the relational aspect in the nursing process may have contributed to the limited focus on the patient's perspective in documented nursing care. Research reports a lack of attention to patients' individual perspectives, preferences, and/or experiences in the documentation of their care (Adamsen & Tewes, 2000;Florin, Ehrenberg, & Ehnfors, 2005). It is acknowledged that personal experiences, preferences, and values need to be integrated and supported to optimize health decisions in the clinical encounter .…”
Section: Clinical Support Systems For the Positive Aspects Of Healthmentioning
confidence: 99%
“…Research reports a lack of attention to patients' individual perspectives, preferences, and/or experiences in the documentation of their care 5,6 . It is acknowledged that personal experiences, preferences, and values need to be integrated and supported to optimize health decisions in the clinical encounter 7 .…”
Section: Introductionmentioning
confidence: 99%